BANKING SUPPORT AND DIGITAL FINANCING: ANALYSIS ON THE IMPACT OF MSMEs DEVELOPMENT IN INDONESIA - Veronica Swasti Paramitha (Bajang Institute, 2026)
This paper examines the evolution of funding sources for SMEs in Indonesia from 2015 to 2024, emphasizing bank financing, People's Business Credit (KUR), fintech lending, and securities crowdfunding (SCF). A quantitative method utilizing a fixed-effect model was employed to identify the relationships among the variables. The Financial Services Authority (OJK) and Bank Indonesia (BI) provided data that includes annual statistics on SME loans, total banking credit, KUR disbursements, fintech lending distribution, and SCF funding. The results demonstrate that both banking assistance and digital finance substantially enhance funding for SMEs. This underscores the importance of merging conventional banking practices with digital financial options to enhance capital accessibility for a wider demographic. This integration enables loan procurement for small and medium-sized firms and is essential for guaranteeing nationwide access to financial services. By amalgamating these two revenue generation approaches, Indonesia can improve access to financial services for small firms, which are vital for the nation's economic advancement. This study indicates that strengthening partnerships between conventional financial institutions and fintech can promote sustainable growth for SMEs and further Indonesia's financial inclusion objectives.